Aplicação da NR-18 em canteiros de obra: percepções e estudos de campo - Sant'Anna Junior, Rubens (2013)
The regulatory norm 18 (NR-18), entitled Conditions and work environment in the construction industry, is the reference to be followed for the national construction companies provide adequate conditions of hygiene and safety in construction sites and for extension, not punished by federal labor inspection. Civil construction is an industry with a high risk of accidents, whose occurrence continues to cause harm to the worker, the company and the government and it becomes important to evaluate the adequacy of the norm to this situation. This research aimed to identify the main difficulties found in attendance the NR-18 by construction companies of Buildings subsector, located in the metropolitan region of Vitória, the capital of Espírito Santo, in a study motivated by lack of information about it. It was applied the method of field research in four construction companies, using a checklist of compliance with NR-18 in a construction site by company. Then, semi-structured interviews were conducted with entrepreneurs, engineers and technicians work safety of the visited companies to know their perceptions and attitudes about work safety and compliance with NR-18. The results indicated the norm items with most difficult to be complied by companies; verifying that the causes of failure are more of a managerial nature and culture of the workers than the rigor of the requirements contained in the norm; that the four companies surveyed have obtained high grades of compliance with NR-18, which are higher than the average grades achieved by peer companies located in other Brazilian cities and proposed suggestions for reducing the causes of noncompliance of the norm. It can be concluded that although it needs adjustments for unforeseen situations and review the text to avoid some words causing differing interpretations, the norm has good applicability and is an important instrument in favor of work safety in the construction industry.